(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
We have very little evidence of female presence within the popular audience of epic-chivalric public performances: a statistical issue, related to the scarcity of surviving evidence, or a more significant indicator? The essay attempts to answer this question through a parallel between the reception of 15th-16th century chivalric narratives and 19th-20th century southern Italian popular performances (cantarinaldi, cunto, opera dei pupi). Even between such distant ages, there are a great many points of contact in the reception of chivalric narratives. They allow us to emphasize, on the one hand, the tendency to perceive the epic-chivalric spectacle as a “private” space for male audiences (in which they could indulge in sentiment and identification), and, on the other hand, the unconditional love that women developed for this narrative universe as soon as they had the chance to get to know it.